Unglazed Ceramics with Mountain Goat Figures of Ani - Muhammet Arslan; Ahmet Şen (Art-Sanat)
Ani, which forms the western border of the historical Arran geography, entered a new era with the Seljuk conquest by Sultan Alparslan in 1064. This period, which constitutes the second prosperity period after the Bagratuni Dynasty; is a period in which political, commercial, social and artistic breakthroughs took place in the city. Archaeological excavations ongoing here are important in terms of revealing the rich artistic activity in the 11th and 12th centuries, which constituted the second prosperity period of Ani. The richness of the ceramic finds obtained during the excavations, on the one hand, reveals the qualified style of the period, on the other hand, offers important clues about the traces of life in the city. Some of the unglazed ceramic fragments from the ceramic finds are also important with their figural ornaments. These pieces which form the borders around the body of a large cube were produced from red and brown clay. There are human depictions along with various animal figures embroidered with cylindrical seal printing techniques on them. Most of the animal figures are mountain goat figures. It is not a coincidence that the goat, which has been famous for its courage and freedom since the first nomadic Turkish communities, finds a place for itself in Ani ceramics. These mountain goats which are usually depicted with human and plant motifs as well as other animal figures in motion and a flowing scene are considered to be a product of the Arran School in the Middle Ages. The existence of such rich ceramic fragments in Ani is important in terms of revealing the existence of a ceramic kiln representing this school in the city.